2021
DOI: 10.1177/0018726721990438
|View full text |Cite
|
Sign up to set email alerts
|

Be smart, play dumb? A transactional perspective on day-specific knowledge hiding, interpersonal conflict, and psychological strain

Abstract: Research on knowledge hiding, the intentional attempt to withhold knowledge that others have requested, strikingly shows its detrimental consequences. But, if it has only negative effects, why do employees hide knowledge in their everyday work at all? With this diary study, we address this question, shedding light on the instrumentality of knowledge hiding. Specifically, placing it within the transactional stress model, we argue that deceptive knowledge hiding (playing dumb and evasive hiding) may function as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 89 publications
(219 reference statements)
3
80
0
Order By: Relevance
“…Apart from knowledge hiding, relationship conflicts in organizations result in performance disruption, low productivity, low motivation, absenteeism, and turnovers [55][56][57][58]. The findings are consistent with the literature, as Venz and Nesher Shoshan [59] identified that employees would hide their knowledge when they experience interpersonal conflicts. In the same vein, data support hypothesis 2 and confirm that relational conflicts create frustration, which is a counterproductive emotion.…”
Section: Discussionsupporting
confidence: 85%
“…Apart from knowledge hiding, relationship conflicts in organizations result in performance disruption, low productivity, low motivation, absenteeism, and turnovers [55][56][57][58]. The findings are consistent with the literature, as Venz and Nesher Shoshan [59] identified that employees would hide their knowledge when they experience interpersonal conflicts. In the same vein, data support hypothesis 2 and confirm that relational conflicts create frustration, which is a counterproductive emotion.…”
Section: Discussionsupporting
confidence: 85%
“…It might even be that when specific demands are pressing (e.g. high e‐mail volume), leaders might not simply refrain from transformational leadership but in fact cut back transformational behaviours (see Trougakos et al, 2015 , for a similar reasoning) to save energy resources from being overused (see Venz & Nesher Shoshan, 2021 , for an example of such a mechanism of day‐specific coping). Considering these ideas, we deem it interesting for future studies to shed light on the role that state exhaustion plays in predicting dynamic leader behaviour, how exhaustion and transformational leadership are related reciprocally within and between days, and what effects day‐specific e‐mail demands and their appraisal have in this conjunction.…”
Section: Discussionmentioning
confidence: 99%
“…We measured end‐of‐work exhaustion with the five‐item physical fatigue subscale of the Shirom‐Melamed Burnout Measure (Shirom & Melamed, 2006 ), in a German version adapted to day‐specific assessment (Venz & Nesher Shoshan, 2021 ). Participants indicated how they “feel at the moment.” A sample item is “I feel tired.” Mean Cronbach's alpha was .89; ICC was .62.…”
Section: Methodsmentioning
confidence: 99%
“…Within-person variables. Following recommended practices for daily diary studies (Lanaj, Johnson, & Barnes, 2014;Matta, Erol-Korkmaz, Johnson, & Biçaksiz, 2014;Niks, de Jonge, Gevers, & Houtman, 2017;Rodell & Judge, 2009;Venz & Shoshan, 2021), we utilized a short version of scales to measure daily time-pressure, daily ego depletion, daily knowledge sharing, and daily knowledge-hiding behavior. Ohly, Sonnentag, Niessen, and Zapf (2010) suggested that three-item scales are more appropriate to measure daily variables than scales with five or more items, to minimize respondent fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the statistical procedure are outlined in Zhang, Zyphur, and Preacher (2009) and Hayes and Rockwood (2020). Due to the small sample size, we used a restricted maximum likelihood model (McNeish, 2017) and a random-intercept fixed-slope model (Venz & Shoshan, 2021;Wehrt, Casper, & Sonnentag, 2020), following previous studies and recommended practice.…”
Section: Analytic Strategymentioning
confidence: 99%